Clonidine stimulates force of contraction via histamine H2 receptors in the human atrium - Joachim Neumann; Steffen Pockes; Laura J. Humphrys; Denise Mönnich; Lisa Forster; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Clonidine has various clinical effects mediated by agonism of α 1 - or α 2 -adrenoceptors and the blocking of hyperpolarization-activated-nucleotide-gated pacemaker channels (HCN). It is unknown whether clonidine can also stimulate human cardiac histamine H 2 receptors (hH 2 Rs). We used isolated electrically stimulated left and spontaneously beating right atrial preparations from mice overexpressing the hH 2 R specifically in the heart (H 2 -TG), and spontaneously beating right atrial preparations of guinea pigs for comparison. Moreover, we studied isolated electrically stimulated muscle strips from the human right atrium. Clonidine (1, 3, and 10 µM) increased force of contraction in isolated left atrial preparations from H 2 -TG mice. In contrast, clonidine reduced the spontaneous beating rate in right atrial preparations from H 2 -TG. Clonidine raised the beating rate in guinea pig right atrial preparations. Clonidine failed to increase the force of contraction but reduced beating rate in wild-type litter mate mice (WT). In WT, histamine failed to increase the force of contraction in left atrial preparations and beating rate in right atrial preparations. Clonidine (10 µM) increased the force of contraction in isolated human right atrial preparations. The positive inotropic effect in the human atrium was attenuated by cimetidine (10 µM). Clonidine increased the beating rate of the isolated spontaneously beating guinea pig right atrium and acted as a H 2 R partial agonist. Furthermore, clonidine showed binding to the guinea pig H 2 R (100 µM) using HEK cells in a recombinant expression system (p K i < 4.5) but hardly to the human H 2 R. These data suggest that clonidine can functionally activate cardiac human H 2 R.

Ergometrine stimulates histamine H2 receptors in the isolated human atrium - Hannes Jacob; Pauline Braekow; Britt Hofmann; Uwe Kirchhefer; Lisa Forster; Denise Mönnich; Laura J. Humphrys; Steffen Pockes; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Ergometrine (6a R ,9 R )- N -(( S )-1-hydroxypropan-2-yl)-7-methyl-4,6,6a,7,8,9-hexa-hydro-indolo-[4,3- fg ]chinolin-9-carboxamide or lysergide acid β-ethanolamide or ergonovine) activates several types of serotonin and histamine receptors in the animal heart. We thus examined whether ergometrine can activate human serotonin 5-HT 4 receptors (h5-HT 4 R) and/or human histamine H 2 receptors (hH 2 R) in the heart of transgenic mice and/or in the human isolated atrium. Force of contraction or beating rates were studied in electrically stimulated left atrial or spontaneously beating right atrial preparations or spontaneously beating isolated retrogradely perfused hearts (Langendorff setup) of mice with cardiac specific overexpression of the h5-HT 4 R (5-HT 4 -TG) or of mice with cardiac specific overexpression of the hH 2 R (H 2 -TG) or in electrically stimulated human right atrial preparations obtained during cardiac surgery. Western blots to assess phospholamban (PLB) phosphorylation on serine 16 were performed. Ergometrine exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in atrial preparations starting at 0.3 µM and reaching a plateau at 10 µM in H 2 -TGs ( n = 7). This was accompanied by an increase in PLB phosphorylation at serine 16. Ergometrine up 10 µM failed to increase force of contraction in left atrial preparations from 5-HT 4 -TGs ( n = 5). Ten micrometer ergometrine increased the force of contraction in isolated retrogradely perfused spontaneously beating heart preparations (Langendorff setup) from H 2 -TG but not 5-HT 4 -TG. In the presence of the phosphodiesterase inhibitor cilostamide (1 µM), ergometrine at 10 µM exerted positive inotropic effects in isolated electrically stimulated human right atrial preparations, obtained during cardiac surgery, and these effects were eliminated by 10 µM of the H 2 R antagonist cimetidine but not by 10 µM of the 5-HT 4 R antagonist tropisetron. Furthermore, ergometrine showed binding to human histamine H 2 receptors (at 100 µM and 1 mM) using HEK cells in a recombinant expression system (p K i < 4.5, n = 3). In conclusion, we suggest that ergometrine is an agonist at cardiac human H 2 Rs.

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Taxon-specific multiplex-PCR for quick, easy, and accurate identification of encyrtid and aphelinid parasitoid species attacking soft scale insects in California citrus groves - Paul F. Rugman-Jones; Lisa D. Forster; Emilio Guerrieri; Robert F. Luck; Joseph G. Morse; Maurilia M. Monti; Richard Stouthamer (BioControl, 2011)